2015
DOI: 10.1103/physreva.91.012103
|View full text |Cite
|
Sign up to set email alerts
|

One-state vector formalism for the evolution of a quantum state through nested Mach-Zehnder interferometers

Abstract: Linear-optical interferometers play a key role in designing circuits for quantum information processing and quantum communications. Even though nested Mach-Zehnder interferometers appear easy to describe, there are occasions when they provide unintuitive results. This paper explains the results of a highly discussed experiment performed by Danan et al. [Phys. Rev. Lett. 111, 240402 (2013)] using a standard approach. We provide a simple and intuitive one-state vector formalism capable of interpreting their exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…In particular, it rules out the option of a continuous trajectory. The results have stirred a lively discussion in the literature [22][23][24][25][26][27][28][29][30][31][32][33] including criticism on the use of classical light and the sensitivity of the experiment. Unfortunately, the clever technique used for obtaining the "which path" information, could not be applied to single photons.…”
Section: Operational Definition Of Photonic Trajectorymentioning
confidence: 99%
“…In particular, it rules out the option of a continuous trajectory. The results have stirred a lively discussion in the literature [22][23][24][25][26][27][28][29][30][31][32][33] including criticism on the use of classical light and the sensitivity of the experiment. Unfortunately, the clever technique used for obtaining the "which path" information, could not be applied to single photons.…”
Section: Operational Definition Of Photonic Trajectorymentioning
confidence: 99%
“…1) and measuring the time varying intensity difference across two halves of a quad-cell detector placed at one of the outputs. This has generated much interest in both theoretical [3,4] and experimental [5][6][7][8][9][10][11] contexts due mainly to the controversial conclusion that the photons follow disconnected paths in the interferometer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Danan et al, in the supplementary material appended to their paper [13], have themselves shown that there is a non-negligible leakage by blocking light from mirror F and observing the peaks corresponding to mirrors A and B disappear, although this was interpreted by them as evidence for the lack of electronic noise in the set-up. Bartkiewicz et al [11] have attempted to provide a minimal fully quantum treatment working in the frequency domain only. However they have assumed that the effect of the vibrating mirrors is to imprint the which-way information using mutually orthogonal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The surprising results of the experiment reported in [8] were actively discussed in [13][14][15][16][17][18][19], where their interpretation was criticized and various modifications of the experiment and methods of data processing were proposed. The authors of [8] also reported the calculation of detected signals according to the classical theory of electromagnetic waves but did not find any simple interpretation of the signals within this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [8] also reported the calculation of detected signals according to the classical theory of electromagnetic waves but did not find any simple interpretation of the signals within this approach. The authors of [19] proposed to describe the evolution of the state of photons within a modified scheme according to traditional quantum mechanics. A numerical-analytical description of the discussed experiment was given in [17] on the basis of the paraxial optical approximation and angular spectrum.…”
Section: Introductionmentioning
confidence: 99%